Step-by-step explanation:
The general equation is y = mx + c...
The given equation is 2x + y = 6
Firstly, move everything on the left except the y to the right.i.e.
y = 6 - 2x
Secondly, rearrange the values on the right to look just like the general equation.
y = -2x + 6
The equation is now in proper general form because it matches the format laid down.
The equilateral triangle pool: height 52ft and base 60ft
A. f(x) = -3(1/5)^x-1
B. f(x) = -3(1/5)^x-1
C. f(x) = -1/5(3)^x-1
D. f(x) = -1/5(-3)^x-1
The one that has the -1/5 inside is the one.
each term is multiplied by -1/5.
The first term is -3
for a_1=first term
r=common ratio
n=which term
In this case
The first term=-3
The common ratio is -1/5
so,
None of them A and B are the same
The one that has the -1/5 inside is the one.
To learn more about the sequence visit:
#SPJ5
The area of circle Q's sector = 4π
the area of circle R's sector = 9π
The radius of circle Q = 7 cm
We need to find the radius of circle R that is x
Given : Both circle Q and circle R have a central angle measuring 110°
So the radius of circle R to the radius of circle Q is equal to the square root (area of circle R to the radius of circle Q)
Plug in all the values
Therefore , the radius of circle R = 10.5 cm